SOSIALISASI ETIKA PUBLIKASI PENULISAN ARTIKEL ILMIAH PADA GURU SEKOLAH DASAR DI DUSUN BANGUN HARJO - Tri Wiyoko; Randi Eka Putra; Mulza Rois (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2020)
The ability of teachers from the aspects of writing, reading and adding scientific insights is really demanded in the current era. If the teacher does not have the ability to write scientific papers and publish it is certainly hampered for promotion / class. Based on this, it is necessary to socialize ethics publication of scientific article writing for teachers in elementary schools. The socialization was carried out in the Bangun Harjo hamlet with the participants of the elementary school teachers. The socialization was carried out in three stages; 1) Preparation, the preparatory stage includes gathering material and making material in the form of powerpoints. 2) Implementation of Socialization, stages of the implementation of socialization with lecture, discussion and question and answer techniques 3) Evaluation, this stage is carried out by giving questionnaires to respondents. The results of this socialization show that 1) Participants for the first time participated in the socialization ethics publication activities so that it is very helpful in writing scientific papers, 2) Participants feel the benefits of the material provided. 3) Participants are very satisfied with this socialization activity and are willing to take part in further socialization.